COVID-19 pandemics Stage II – Energy and environmental impacts of vaccination. (October 2021) - Klemeš, Jiří Jaromír; Jiang, Peng; Fan, Yee Van; Bokhari, Awais; Wang, Xue-Chao
Abstract: The COVID-19 pandemic developed the severest public health event in recent history. The first stage for defence has already been documented. This paper moves forward to contribute to the second stage for offensive by assessing the energy and environmental impacts related to vaccination. The vaccination campaign is a multidisciplinary topic incorporating policies, population behaviour, planning, manufacturing, materials supporting, cold-chain logistics and waste treatment. The vaccination for pandemic control in the current phase is prioritised over other decisions, including energy and environmental issues. This study documents that vaccination should be implemented in maximum sustainable ways. The energy and related emissions of a single vaccination are not massive; however, the vast numbers related to the worldwide production, logistics, disinfection, implementation and waste treatment are reaching significant figures. The preliminary assessment indicates that the energy is at the scale of ~1.08 × 10 10  kWh and related emissions of ~5.13 × 10 12 gCO2eq when embedding for the envisaged 1.56 × 10 10 vaccine doses. The cold supply chain is estimated to constitute 69.8% of energy consumption of the vaccination life cycle, with an interval of 26–99% depending on haul distance. A sustainable supply chain model that responds to an emergency arrangement, considering equality as well, should be emphasised to mitigate vaccination's environmental footprint. This effort plays a critical role in preparing for future pandemics, both environmentally and socially. Research in exploring sustainable single-use or reusable materials is also suggested to be a part of the plans. Diversified options could offer higher flexibility in mitigating environmental footprint even during the emergency and minimise the potential impact of material disruption or dependency. Highlights: The fight with the COVID-19 pandemics is entering the offensive stage. The global vaccination campaign is a large and demanding operation. It requires substantial energy and related emissions. It is a strong need to minimise the environmental impacts now and for the future. Assessments indicate ~1.08 × 10 10  kWh and emissions of ~5.13 × 10 12 gCO2eq for 1.56 × 10 10 vaccines.